B cell lymphoma progression promotes the accumulation of circulating Ly6Clo monocytes with immunosuppressive activity. (1st February 2018) - McKee, Sara J.; Tuong, Zewen K.; Kobayashi, Takumi; Doff, Brianna L.; Soon, Megan SF; Nissen, Michael; Lam, Pui Yeng; Keane, Colm; Vari, Frank; Moi, Davide; Mazzieri, Roberta; Leggatt, Graham; et al.
ABSTRACT: Monocytosis is considered a poor prognostic factor for many cancers, including B cell lymphomas. The mechanisms by which different monocyte subsets support the growth of lymphoma is poorly understood. Using a pre-clinical mouse model of B cell non-Hodgkin's lymphoma (B-NHL), we investigated the impact of tumor progression on circulating monocyte levels, subset distribution and their activity, with a focus on immune suppression. B-NHL development corresponded with significant expansion initially of classical (Ly6Chi) and non-classical (Ly6Clo) monocytes, with accumulation and eventual predominance of Ly6Clo cells. The lymphoma environment promoted the conversion, preferential survival and immune suppressive activity of Ly6Clo monocytes. Ly6Clo monocytes expressed higher levels of immunosuppressive genes including PD-L1/2, Arg1, IDO1 and CD163, compared to Ly6Chi monocytes. Both monocyte subsets suppressed CD8 T cell proliferation and IFN-γ production in vitro, but via different mechanisms. Ly6Chi monocyte suppression was contact dependent, while Ly6Clo monocytes suppressed via soluble mediators, including IDO and arginase. Ly6Clo monocytes could be selectively depleted in tumor-bearing hosts by liposomal doxorubicin treatment, further enhanced by co-administration of anti-4-1BB monoclonal antibody. This treatment led to a reduction in tumor growth, but failed to improve overall survival. Analogous immunosuppressive monocytes were observed in peripheral blood of diffuse large B cell lymphoma patients and actively suppressed human CD8 T cell proliferation. This study highlights a potential immune evasion strategy deployed by B cell lymphoma involving accumulation of circulating non-classical monocytes with immunosuppressive activity.